Ukuran Letak - Puspita, Laila Dwi; Putri, Saskia Amanda; Panggabean, Hadi Saputra (CV. Rayyan Dwi Bharata, 2025)
This study aims to examine the concept and application of measures of position in educational statistics. Measures of position include quartiles, deciles, and percentiles, which are used to determine the relative position of a value within a data distribution. The research methodology employed is a literature review by analyzing various relevant sources, including educational statistics textbooks and scientific articles. The results of the discussion indicate that measures of position are essential in analyzing students' academic achievement, as they provide a detailed picture of data distribution. The main issue addressed in this study is the lack of students’ understanding regarding the application of measures of position in educational contexts. The data analyzed were derived from literature studies and examples of how measures of position are applied in analyzing students' exam scores. The conclusion of this study is that understanding measures of position can help educators and researchers assess individual achievements within a group more fairly and accurately.